Association between immune-inflammatory index and osteoporosis: a systematic review and meta-analysis - Bihui Bai; Xingwen Xie; Yongyu Yue; Jiahe Cui; Fangfang Xie; Fei Yao (European Journal of Medical Research)
Abstract Objective Plenty of evidence proves the prospective diagnostic and prognostic utility of inflammatory markers in osteoporosis (OP). However, the relations of immune-inflammatory indices to OP remain elusive, with scarce conclusive evidence-based findings. Our systematic review and meta-analysis endeavored to unveil the links between immune-inflammatory indices and OP. Methods PubMed, Web of Science, Embase, as well as Cochrane Library, were thoroughly retrieved for research investigating the links of immune-inflammatory indices to OP, from database inception to February 20, 2025. Data were analyzed using odds ratio (OR), standardized mean difference (SMD), as well as corresponding 95% confidence interval (CI). Sensitivity and subgroup analyses were carried out for result robustness evaluation and heterogeneity source identification. Review Manager 5.4 and STATA 18.0 were utilized in every statistical analysis. Results A total of 24 studies were included in this analysis. Eight cohort studies and 16 case–control studies based on 397,525 subjects and 11,904 cases were eventually screened and retained. The findings indicated significant positive relations of immune-inflammatory indices to OP risk. For categorical variables, elevated neutrophil-to-lymphocyte ratio (NLR) (OR = 2.34, 95% CI 1.77–3.11; P < 0.00001), platelet-to-lymphocyte ratio (PLR) (OR = 1.05, 95% CI 1.01–1.08; P = 0.01), as well as systemic immune-inflammation index (SII) (OR = 1.16, 95% CI 1.04–1.30; P = 0.01) notably correlated with a increased OP risk. For continuous variables, individuals with OP exhibited significantly higher levels of NLR (SMD = 0.71, 95% CI 0.35–1.07; P = 0.0001), PLR (SMD = 0.43, 95% CI 0.17–0.68; P = 0.001), monocyte-to-lymphocyte ratio (MLR) (SMD = 0.54, 95% CI 0.16–0.91; P = 0.005), and SII (SMD = 0.25, 95% CI 0.03–0.47; P = 0.03) compared to non-OP populations. Subgroup analyses revealed that geographic region and age were major contributing factors influencing the association between immune-inflammatory indices and OP. Conclusion Immune-inflammatory indices such as NLR, PLR, MLR, and SII are significantly linked to increased risk of OP. These indices may facilitate the early identification of individuals at high risk for OP and support timely preventive strategies. Given the inherent limitations of the current study, further prospective, multicenter clinical investigations are warranted to validate the relations of immune-inflammatory indices to OP. Trial registration Systematic review registration: PROSPERO, identifier: CRD420250656296.